Construction and evaluation of thoracic injury risk curves for a finite element human body model in frontal car crashes. (December 2015) - Mendoza-Vazquez, Manuel; Davidsson, Johan; Brolin, Karin
Highlights: Injury risk curves for two or more fractured ribs were constructed and evaluated for an FE-HBM. The injury risk curves for shear stress and DcTHOR performed best among the 14 constructed curves. Shear stress injury risk curve was more sensitive to changes in rib material properties than DcTHOR. Age adjusted injury risk curves for two or more fractured ribs are provided for an FE-HBM. Abstract: There is a need to improve the protection to the thorax of occupants in frontal car crashes. Finite element human body models are a more detailed representation of humans than anthropomorphic test devices (ATDs). On the other hand, there is no clear consensus on the injury criteria and the thresholds to use with finite element human body models to predict rib fractures. The objective of this study was to establish a set of injury risk curves to predict rib fractures using a modified Total HUman Model for Safety (THUMS). Injury criteria at the global, structural and material levels were computed with a modified THUMS in matched Post Mortem Human Subjects (PMHSs) tests. Finally, the quality of each injury risk curve was determined. For the included PMHS tests and the modified THUMS, DcTHOR and shear stress were the criteria at the global and material levels that reached an acceptable quality. The injury risk curves at the structural level did not reach an acceptable quality.